+0  
 
+1
123
2
avatar

use substitution to solve the system

 

-5x + 2y = -18

y=2x-7 

 Mar 3, 2021
 #1
avatar+570 
0

we can substitute 2y for 2(2x-7), and we get

 

-5x+4x-14=-18

-x=-4

x=$\boxed{4}$

 

now, we can plug in x in the equation y=2x-7:

 

y=8-7=$\boxed1$

 Mar 3, 2021
 #2
avatar+2 
0

We can substitute $x$ for $\frac{18+2y}{5}$. So we have $y=2(\frac{18+2y}{5} -7.$ That simplifies to $y=\frac{36+4y}{5}-7$, or $y+7=\frac{36+4y}{5}.$ We don't like fractions, so therefore, we can multiply the whole equation by $5$, to get $35+5y=36+4y$, or $y=\boxed{1}.$ To solve for $x$, we can substitute: $$x=\frac{18+2y}{5}=\frac{18+2}{5} = \frac{20}{5}=\boxed{4},$$ so $(x,y)=(4,1).$

 Mar 3, 2021
edited by lordofeverything  Mar 3, 2021
edited by lordofeverything  Mar 3, 2021

25 Online Users

avatar
avatar